Implementasi AI dalam Proses Pembelajaran pada Mahasiswa Semster Awal Pendidikan Bahasa Inggris - Hidayatullah, Rizky (CV. Bimbingan Belajar Assyfa, 2024)
The implementation of artificial intelligence (AI) in the learning process has become an essential innovation in education, including English language learning for first-semester students in English Education programs. This study aims to examine the impact of AI usage in enhancing the effectiveness and efficiency of English language learning for these students. AI applications in learning cover various aspects, such as automatic translation, speech recognition, and interactive applications that support language skills development. With AI, students can receive instant feedback, access materials independently, and develop language skills in a more structured manner. This study employs a qualitative descriptive method, collecting data through interviews and observations with first-semester students who have used AI as a supportive learning tool. The findings indicate that AI implementation positively influences learning motivation, comprehension of material, and the improvement of speaking, listening, and writing skills in English. However, challenges remain in its application, such as limited access to technology and adaptability to AI platforms. In conclusion, AI implementation can significantly enhance the quality of English language learning, especially in the early stages of university studies, if integrated appropriately into the curriculum and supported by adequate facilities and training.